2010
DOI: 10.1007/s10787-010-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective potentials of candesartan, atorvastatin and their combination against stroke induced motor dysfunction

Abstract: Cerebral ischaemia is a leading cause of death and disability. The objective of the present investigation was to explore the neuroprotective potentials of candesartan and atorvastatin alone and their combination against the cerebral ischaemia induced behavioral, biochemical, and mitochondrial dysfunction. Male Wistar rats (200-220 g) were subjected to bilateral common carotid artery occlusion for 30 min followed by 24 h reperfusion. Candesartan (0.1 and 0.3 mg/kg) and atorvastatin (10 and 20 mg/kg) were pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…In accordance to this, Ludka et al demonstrated that a single administration of atorvastatin in a range dose of 0.01 to 30 mg/kg, did not cause any changes in locomotor parameters [40]. It has been shown that 1 week of atorvastatin treatment (10 and 20 mg/kg) improved the deficit promoted by stroke in the locomotors patterns, but atorvastatin per se did not cause any changes in OF [41]. The literature demonstrates that 2 weeks of simvastatin treatment do not change exploratory patterns in open field in rats, however 4 weeks of simvastatin (10 mg/kg) treatment promotes an increase in distance traveled in the open field task [14,19].…”
Section: Discussionmentioning
confidence: 78%
“…In accordance to this, Ludka et al demonstrated that a single administration of atorvastatin in a range dose of 0.01 to 30 mg/kg, did not cause any changes in locomotor parameters [40]. It has been shown that 1 week of atorvastatin treatment (10 and 20 mg/kg) improved the deficit promoted by stroke in the locomotors patterns, but atorvastatin per se did not cause any changes in OF [41]. The literature demonstrates that 2 weeks of simvastatin treatment do not change exploratory patterns in open field in rats, however 4 weeks of simvastatin (10 mg/kg) treatment promotes an increase in distance traveled in the open field task [14,19].…”
Section: Discussionmentioning
confidence: 78%
“…Either candesartan or EGCG exhibited potent antioxidant activity and decreased gentamicin‐induced nephrotoxicity, which was verified by restoring the oxidative balance. There are different experimental studies which demonstrated their antioxidant effects …”
Section: Discussionmentioning
confidence: 99%
“…There are different experimental studies which demonstrated their antioxidant effects. [38,[41][42][43][44] Inflammatory progression induced by gentamicin was evident also by the notable elevation in renal levels of key inflammatory cytokines;…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of rt-PA in combination with aspirin, it is a common and effective treatment against stroke in clinical now. Besides, Candesartan with atorvastatin 38, Memantine with Clenbuterol 39 and Vitamin Dhormone (VDH) with progesterone (P4) can protect brain from stroke 40. Beyond the combination in clinical drugs, drug with peptid can treat acute stroke better as well 41.…”
Section: Discussionmentioning
confidence: 99%